Learning Mathematics of Hadith Integration For Build Character Students in Elementary School - Supiarmo, M. Gunawan; Gilang Primajati; Eka Kurniawan; Dita Oktavihari (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Education has role important in to form personality and character students. However align education academic with education based on character is challenge big for teachers. Considering condition Indonesian students and teenagers who experience crisis ethics and morals. The fact is that students and teenagers often become​ perpetrator action criminal, immoral, abuse drugs, socializing free and other violations that are detrimental self yourself and the environment. So it is necessary existence effort in development and change curriculum in school for to plant values Islam use build character students. One of the its shape is with implement learning mathematics integration hadith. Awareness about importance planting Islamic values in particular mark hadith in build character student should become teacher priorities in learning mathematics. This is Because learning mathematics integration hadith no only know about knowledge mathematics but also get character education.